A novel mouse model for the aggressive variant of NK cell and T cell large granular lymphocyte leukemia - Yokohama, Akihiko (2009)
Murine models of disease are vital to the understanding of pathogenesis and the development of novel therapeutics. We have previously established interleukin (IL)-15 transgenic (tg) mice that demonstrate rapid proliferation of natural killer (NK) and T cells, followed by spontaneous transformation to lethal leukemia. Herein, we have characterized this model, which has many features in common with the aggressive variants of NK and T large granular lymphocyte leukemia (LGLL) in humans. The LGLL blasts are cytolytic and produce IFN-γ ex vivo. Cytogenetic analysis revealed trisomy of chromosome 17 and/or 15. This model should provide opportunities to develop effective standard therapies for this fatal disease.